Peran kepribadian dan orientasi budaya (individualis vs. kolektivis) terhadap perilaku inovatif individual pada pegawai - Nurmala, Sukma; Mashuri, Ali (Jurnal Psikologi Sosial, 2025)
Individual innovative behavior reflects the exploration and application of new ideas in the work environment. Personality and cultural orientation (individualism vs. collectivism) play an important role in shaping an employee's innovative tendencies. Unfortunately, most current research still examines personality factors and cultural orientation factors separately, even though both factors have great potential to be interrelated in predicting individual innovative behavior. Therefore, this study aims to analyze the influence of personality and cultural orientation on individual innovative behavior in the workplace. This study uses a quantitative approach with a survey method. The sampling technique used is purposive sampling, with a total of 265 participants who are employees with at least one year of work experience. The research instruments consisted of the individual innovative behavior scale, the IPIP-BFM-25 Indonesia Scale, and the cultural orientation scale. The results of the study showed that individualist orientation, intellect personality, and conscientiousness were significantly related to the tendency of innovative behavior. Individuals who are open to new experiences, tend to be individualistic, have strong self-discipline, and have a high level of education are more likely to show innovative behavior. In addition, these characteristics are more often observed in male employees. Meanwhile, collectivism did not show a significant relationship with innovative behavior. These findings have important implications, both theoretically and practically. Theoretically, this study confirms that personality and culture orientation can play a role in shaping innovative behavior, although there is variation in their effects. Practically, these results indicate the importance of developing human resource management strategies that can encourage innovation by considering individual factors and work culture.